2016
DOI: 10.21767/2572-5459.100008
|View full text |Cite
|
Sign up to set email alerts
|

Antioxidant Systems in Poultry Biology: Superoxide Dismutase

Abstract: Commercial poultry production is associated with various stresses responsible for decreasing productive and reproductive performance of growing chicks, breeders and commercial layers. A growing body of evidence shows that most of stresses in poultry production at the cellular level are associated with oxidative stress. Recently, a concept of the cellular antioxidant defense has been revised with special attention paid to cellular redox status maintenance and cell signaling. In fact, antioxidant systems of the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
151
2
7

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 168 publications
(163 citation statements)
references
References 139 publications
(166 reference statements)
3
151
2
7
Order By: Relevance
“…Particularly, GST catalyses the conjugation of GSH to a variety of endogenous and exogenous electrophilic compounds [41]. The SOD is an important enzyme involved in the oxidative stress and provides protection against lipid peroxidation [42]. Catalase is an iron containing enzyme which catalyses the breakdown of hydrogen peroxide, a harmful agent for the cells.…”
Section: Discussionmentioning
confidence: 99%
“…Particularly, GST catalyses the conjugation of GSH to a variety of endogenous and exogenous electrophilic compounds [41]. The SOD is an important enzyme involved in the oxidative stress and provides protection against lipid peroxidation [42]. Catalase is an iron containing enzyme which catalyses the breakdown of hydrogen peroxide, a harmful agent for the cells.…”
Section: Discussionmentioning
confidence: 99%
“…Among these factors, high stocking density is considered as an important stress factor which has critical implications for the poultry industry (Puron, Santamaria, Segura, & Alamilla, 1995). It is suggested that most of stresses in poultry production at the cellular level are associated with oxidative stress due to excess of free radical production or inadequate antioxidant protection (Surai, 2016). An inadequate physical and social environment can be a source of discomfort and stress (Morgan & Tromborg, 2007).…”
mentioning
confidence: 99%
“…All living cells including spermatozoa regularly face the oxygen paradox. The oxygen is necessary for maintaining life; nevertheless, its metabolites, such as ROS, must be neutralized constantly to support the small amount essential for physiological cell function (Niki, 2014;Surai, 2016). The spermatozoa PUFAs are extremely susceptible to lipid peroxidation, as a result, ROS are produced in high quantity, which are harmful to the fertilizing capability of semen (Agarwal et al, 2003).…”
Section: Free Radicals and Oxygen And Lipid Peroxidationmentioning
confidence: 99%
“…The spermatozoa PUFAs are extremely susceptible to lipid peroxidation, as a result, ROS are produced in high quantity, which are harmful to the fertilizing capability of semen (Agarwal et al, 2003). Due to an increased production of ROS, oxidative stress, which is the imbalance between prooxidants and antioxidants happens (Agarwal et al, 2003;Urso & Clarkson, 2003;Surai, 2016).…”
Section: Free Radicals and Oxygen And Lipid Peroxidationmentioning
confidence: 99%
See 1 more Smart Citation